Mobility corresponding location–aware information services based on embedded RFID platform. (24th February 2012) - Jian, Ming–Shen; Chou, Ta–Yuan; Hsu, Shu Hui
In this paper, a Mobility Corresponding Location–Aware Information Services based on embedded RFID Platform that integrates the existed RFID systems and digital information content services server is proposed. According to user's RFID tag, the platform accesses the remote digital content database and broadcasts the corresponding digital content related to the end–user's personal requirements, locations, or historical user records. On the basis of the mobility prediction, the individual and diverse information services are seamlessly provided to each user. The real test and verification prove that the proposed platform can certainly reduce the construction cost of specific area service system deployment.